2003
DOI: 10.1002/humu.9183
|View full text |Cite
|
Sign up to set email alerts
|

CFTR genotypes in patients with normal or borderline sweat chloride levels

Abstract: In recent years, some patients bearing "atypical" forms of cystic fibrosis (CF) with normal sweat chloride concentrations have been described. To identify the spectrum of mutant combinations causing such atypical CF, we collected the results of CFTR (ABCC7) mutation analysis from 15 laboratories. Thirty patients with one or more typical symptoms of the disease associated with normal or borderline sweat chloride levels and bearing two CFTR mutations were selected. Phenotypes and genotypes of these 30 patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 40 publications
1
49
0
3
Order By: Relevance
“…Each of these variable mutations has been reported in the literature in individuals with a diagnosis of cystic fibrosis, CAVD, and in unaffected carriers of 2 mutations. 15,24,25,34 Geographic differences in the origin of the carrier versus patient referrals may also contribute to the variation in mutation distributions between the groups. The lack of detection in the carrier screening population of mutations identified among patients (e.g., 2307delA, W1089X) is not unexpected given the inherent variability in estimates of low-frequency mutations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each of these variable mutations has been reported in the literature in individuals with a diagnosis of cystic fibrosis, CAVD, and in unaffected carriers of 2 mutations. 15,24,25,34 Geographic differences in the origin of the carrier versus patient referrals may also contribute to the variation in mutation distributions between the groups. The lack of detection in the carrier screening population of mutations identified among patients (e.g., 2307delA, W1089X) is not unexpected given the inherent variability in estimates of low-frequency mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In the carrier screening group, 4 mutations, D1152H, R117H, ⌬I507, and L206W, had frequencies of 3.8% to 6.2%, whereas the same mutations were either observed only once or not at all in the CF patient population. With the exception of ⌬I507, each of these mutations is associated with variable phenotypic expression [21][22][23][24][25][26] and when paired with ⌬F508 has been reported in individuals with cystic fibrosis as well as CAVD. 24 African American CF patient population Table 2 depicts the distribution of 33 CFTR mutations identified in the African American population.…”
Section: Hispanic Cf Carrier Screening Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…5,15,20,21 and is correlated with normal or indeterminate sweat chloride tests. 15,20,22 We surmise that the higher incidence of rare mutations in patients diagnosed as adults may contribute to the delay in diagnosis. In our study, 11% of patients diagnosed as adults with sweat tests reported had normal sweat chloride levels and 13.6% had intermediate levels, thus falling into the previously termed "nonclassic" CF defi nition.…”
Section: Symptoms Leading To Diagnosismentioning
confidence: 99%
“…22 The D1152H/⌬F508 genotype also has been reported in four adults with mild pulmonary symptoms, two with Pseudomonas colonization, and another with pancreatic insufficiency. 23,24 This mutation has also been observed in males with CBAVD. 25,26 However, this mutation was present along with G542X in a fetus with hyperechogenic bowel loops and meconium ileus, suggesting a more severe course would occur in this case.…”
Section: Discussionmentioning
confidence: 77%